2017
DOI: 10.23910/ijbsm/2017.8.2.1800
|View full text |Cite
|
Sign up to set email alerts
|

Soil Organic Carbon Pools as Affected by Land Use Types in Hilly Ecosystems of Manipur

Abstract: Soil organic carbon (SOC) stock is a function of climatic conditions, vegetation and soil characteristics. SOC pool is comprised of labile and recalcitrant pools with varying residence time. Labile pool of SOC is very important as it influences soil quality, soil productivity and also it has an impact on global warming. Surface soil samples were collected on February-March, 2015 from four predominant land-use systems viz., forest, grassland, cultivated (rice) land (>10 years) and jhum land (2 years) of the hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
1
0
1
Order By: Relevance
“…This significantly higher quantity of organic C in the surface soil might be due to highest root densities and increased biological activity (Nair and Chamuah, 1988) [16] . This result was in good agreement with Gebrelibanos and Mohammed (2013) [8] and Meetei et al (2017) [15] . While studying the interaction effect of land uses and soil depth on SOC content, it was observed that the highest SOC content [5.72 g kg -1 ] was recorded at the surface 0-20 cm soil depth of the forest land and the lowest [1.83 g kg -1 ] was obtained at 40-60 cm soil depth of the orchard land which was, however, statistically at par with 40-60 cm depth of fallow land, cultivated rice-potato land, cultivated rice land and pasture land; at par with 20-40 cm depth of fallow land, cultivated rice land, pasture land and orchard land as presented in Table 3.…”
Section: Effects Of Land Uses and Soil Depths On Soil Organic Carbon (Soc)supporting
confidence: 91%
See 1 more Smart Citation
“…This significantly higher quantity of organic C in the surface soil might be due to highest root densities and increased biological activity (Nair and Chamuah, 1988) [16] . This result was in good agreement with Gebrelibanos and Mohammed (2013) [8] and Meetei et al (2017) [15] . While studying the interaction effect of land uses and soil depth on SOC content, it was observed that the highest SOC content [5.72 g kg -1 ] was recorded at the surface 0-20 cm soil depth of the forest land and the lowest [1.83 g kg -1 ] was obtained at 40-60 cm soil depth of the orchard land which was, however, statistically at par with 40-60 cm depth of fallow land, cultivated rice-potato land, cultivated rice land and pasture land; at par with 20-40 cm depth of fallow land, cultivated rice land, pasture land and orchard land as presented in Table 3.…”
Section: Effects Of Land Uses and Soil Depths On Soil Organic Carbon (Soc)supporting
confidence: 91%
“…This result was in good agreement with Gebrelibanos and Mohammed (2013) [8] . Meetei et al (2017) [15] also documented that the SOC content of forest land recorded highest (23.68 g kg -1 ) and however, that of cultivated land recorded lowest (13.13 g kg -1 ). Considering the main effects of soil depths (irrespective of land uses) it was observed that the mean soil organic carbon content was highest in surface 0-20 cm soil depth [4.05 g kg -1 ] and lowest in 40-60 cm soil depth [2.13 g kg -1 ].…”
Section: Effects Of Land Uses and Soil Depths On Soil Organic Carbon (Soc)mentioning
confidence: 93%
“…Menurut Adugna, (2016) KTK merupakan salah satu indikator terpenting kesuburan suatu tanah yang menggambarkan kemampuan tanah untuk meretensi hara sehingga mencegah hara segera hilang tercuci. Oleh karenanya tanah dengan KTK yang tinggi akan memiliki kemampuan atau kapasitas yang tinggi untuk menahan lebih banyak hara dalam bentuk kation sehingga tersedia untuk dapat diserap akar tanaman dalam waktu yang lama (Meetei et al, 2017).…”
Section: Perbaikan Reaksi Biokimia DI Dalam Tanahunclassified